Performance and financing of the corporate sector: The role of foreign direct investment - Adam Geršl (Charles University in Prague, Institute of Economic Studies (IES), 2008)
Foreign direct investment has been one of the main drivers of economic developments over the past few years in Central and Eastern Europe (CEE). Within the ongoing globalization and international division of labor, a large number of foreign companies have established production units in CEE countries to benefit from low labor costs and other advantages. This study looks both in theoretical and empirical terms at whether large foreign presence has also affected domestic firms. Foreign firms might both intentionally and unintentionally influence the productivity, financing and export performance of local firms within the same industry or across industries along the production chain via sub-supplier and client linkages. Economic theory does not suggest unambiguous answer to a question whether the influence is positive or negative. For answering the question, both firm-level and industry-level data on performance, financing and exports and interactions of firms within production chain in the Czech Republic are analyzed.
Keywords: F21; D24; L60; G32; F40; 330; foreign direct investment; productivity; corporate finance; export performance; Unternehmenserfolg; Unternehmensfinanzierung; Produktivität; Direktinvestition; Tschechische Republik